Analysing the impact of retail store attributes on unplanned buying intention with mediating role of shopping enjoyment and store perception: An Empirical study - SATPATHY, DR. SARITA; KARUMURI, DR. VENKATESWARALU; SATPATHY, DR. SUSANTA KUMAR (The journal of contemporary issues in business and government, 2021)
Unplanned buyers are always considered as a dream segment for marketers. many times, consumers buy the product due to their sudden unplanned buying intention rather than their need. That is the reason unplanned buying pattern and behaviour is one of the most demandable topics for investigation by the marketers as well consumer behaviour researcher from last half centuries. This research aim to explore, impact of the combination of store attributes like light ,scent, music, displays and efficient employees and personal attributes like customer’s shopping enjoyment and the effect of their store perception. On customer unplanned buying intention. This research has done by a survey method by collecting data with the help of structured questionnaire. The finding of this study will be helpful to the retailers to plan their investment on store ambience that motivate the store visitors to browse the store for longer time which further help them to do unplanned shopping. At the same time it will guide the marketing researchers to understand the unplanned buyer’s insight and explore some more influencing factors which affect the unplanned buying behaviour as well as post purchase behaviour .